2008
DOI: 10.1016/j.clim.2007.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic innate immune activation as a cause of HIV-1 immunopathogenesis

Abstract: Human immunodeficiency virus (HIV)-1 infection causes progressive impairment of the immune system in humans, characterized by depletion of CD4 T cells and loss of T cell function. Increased markers of T cell activation and lymphoid hyperplasia suggest that chronic T cell activation persists in immunocompromised hosts, and contributes to the exhaustion of immune functions. Here we propose a revision of this hypothesis, in which we suggest that chronic activation of innate immunity may negatively affect adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
168
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(179 citation statements)
references
References 75 publications
(33 reference statements)
5
168
0
5
Order By: Relevance
“…ment likely occurs in HIV-1 infection, in which prolonged activation of pDC by the virus, through a CD4/gp120 interaction, might result in long-term suppression of T cell responses and immune exhaustion through activation of IDO (33). We showed that upregulated type I IFNs in 1-MT-treated mice or IDO 2/2 mice suppress LP-BM5 virus replication (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…ment likely occurs in HIV-1 infection, in which prolonged activation of pDC by the virus, through a CD4/gp120 interaction, might result in long-term suppression of T cell responses and immune exhaustion through activation of IDO (33). We showed that upregulated type I IFNs in 1-MT-treated mice or IDO 2/2 mice suppress LP-BM5 virus replication (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…During HIV infection, HIV replication leads to activation of the innate and adaptive immune systems, generating an inflammatory environment associated with the induction of type I IFN (16). The potential role of type I IFN in HIV pathogenesis and treatment has been studied since the beginning of the HIV epidemic (17).…”
Section: H Uman Immunodeficiency Virus Infection Is Characterizedmentioning
confidence: 99%
“…HIV-mediated depletion of CD4 + T cells is a direct consequence of both productive virus infection [18] and induction of Fas-mediated apoptosis in both HIV-infected and -uninfected cells [19]. In addition to these direct mechanisms of HIV-induced T cell depletion, increasing evidence has implicated chronic activation of plasmacytoid DCs as being an indirect mechanism of T cell dysfunction and cytotoxicity [20,21]. In this setting, pulmonary plasmacytoid DCs interact with HIV via CD4,resulting in internalization of the virus.…”
mentioning
confidence: 99%
“…In this setting, pulmonary plasmacytoid DCs interact with HIV via CD4,resulting in internalization of the virus. In the cell cytoplasm, viral RNA is recognized by intracellular pathogen recognition receptors known as Toll-like receptors (TLRs)-7 and -9 [20][21][22][23], and possibly by the more recently described cytoplasmic pathogen nucleic acid sensors [24]. This leads, in turn, to excessive and sustained production of: i) type I interferon (IFN); ii) the tryptophan catabolizing enzyme, indoleamine 2,3-dioxygenase; and iii) the cytokine, transforming growth factor ÎČ (TGF-ÎČ), all of which contribute to immune dysfunction [20,[25][26][27][28][29][30][31][32][33].…”
mentioning
confidence: 99%